Implementasi Sistem Informasi Administrasi Pembelian, Penjualan, Retur dan Inventaris Produk Kosmetik Toko Beauty Dengan Platform Android - Tommy Sugiarto; Silvia Rostianingsih; Rolly Intan (Jurnal Infra, 2020)
Integrated information system is needed on running a business process. The problem nowadays is there is no information system yet capable of support faster business processes. By using the development of technology, information system can process data which can easily manage business process at company. Nowadays, there are companies that are not using the technology optimally.To solve the problems, Beauty Store needs implementation of integrated information system by mobile is needed. By using the technology, can help in increasing of speed and accuracy when make a transaction. Information system of website and point of sales application can record any transaction of purchasing, selling, return and inventory by detail, so it can be practical and easy to use for transaction. From the analysis of questionnaire and system test, 76% of the respondent stated that the website and point of sales application can easily help to manage data of sales, purchasing, return and inventory, and the rest stated not that easy to help manage transaction data.